Placebo-controlled trial of quinine therapy for nocturnal leg cramps. - Fung, M C (1989)
A prospective, double-blind, placebo-controlled crossover study of the use of quinine for nocturnal leg cramps was carried out in 8 elderly volunteer patients. The patients were randomly assigned to receive either placebo or 200 mg of quinine sulfate by mouth at bedtime. After 4 weeks of treatment and after a one-week washout period, the group taking quinine switched to placebo and vice versa for another 4 weeks. The differences in the number, duration, and severity of cramps and the side effects were compared. All of the patients had fewer cramps and decreased severity and duration of attacks while receiving quinine. Mild side effects developed in only 2 patients, and these subsided without treatment or discontinuing the medication. We conclude that quinine was effective in relieving nocturnal leg cramps in a selected group of elderly patients.